IMPLEMENTATION OF PROBLEM-BASED LEARNING MODEL (PBL) BASED ON REFLECTIVE PEDAGOGY APPROACH ON ADVANCED STATISTICS LEARNING - Sulistyani, Niluh (Sanata Dharma University Yogyakarta, 2018)
Problem-based learning was an alternative learning model that can be implemented in a learning based on Reflective Pedagogy approach. Reflective Pedagogy not only prioritized knowledge aspect but also attitude aspect. This research was aimed to 1) describe the implementation of PBL using cycle of Reflective Pedagogy on Advanced Statistics learning and to 2) describe its influenced based on critical attitude, enthusiasm, and caring for others. The subject of this research was Psychology Student of class A. Data collection was gathered from the questionnaire and the results of student reflection. The result showed that the PBL phases could be well implemented in Advanced Statistics learning using Reflective Pedagogy. From the analysis was concluded that PBL gave influenced in good enough category based on critical attitude, enthusiasm, and caring for others.Â DOI: https://doi.org/10.24071/ijiet.2018.020102